Sinkronik dan Diakronik Kata Taufiq Dalam Al-Qur’an Surat Hud Ayat 88 - Akhmad Mahfud; M. Asy’ari (Lembaga Penelitian, Penerbitan dan Pengabdian kepada Masyarakat (LP3M) IAIFA Kediri, 2025)
The linguistic study of the Qur'an does not only focus on philological or interpretive aspects, but can also be analyzed using the perspective of modern linguistics, one of which is the synchronic-diachronic approach. This article attempts to examine the word Taufiq in the Qur'an using both approaches. The synchronic approach is used to analyze the meaning of taufiq, while the diachronic approach is used to determine the development of the meaning of the word taufiq from pre-Islamic Arabic. Synchronically, the word taufiq is explicitly found in Qs. Hud (11): 88. This is understood as Prophet Shu'aib's acknowledgment that all success, guidance, and ability to follow the path of righteousness come entirely from Allah SWT. This confirms the meaning of taufiq as help from Allah SWT that bridges the will of humans with the will of Allah SWT. Meanwhile, diachronic studies show an interesting dynamic of meaning. In pre-Islamic Arabic, the word refers to conformity, agreement, and success in accordance with certain conditions. However, in the Qur'an, this meaning underwent a shift to become a form of assistance from Allah SWT. Thus, the results of this study show that synchronic analysis clarifies the contextual meaning of taufiq in the Qur'an, while diachronic analysis reveals the dynamics of meaning that developed from pre-Islamic times. This study contributes to the semantic understanding of the Qur'an and opens up space for reflection.